2010
DOI: 10.1093/jhered/esp126
|View full text |Cite
|
Sign up to set email alerts
|

Female Reproductive Success Variation in a Pseudotsuga menziesii Seed Orchard as Revealed by Pedigree Reconstruction from a Bulk Seed Collection

Abstract: The impact of female reproductive success on the mating system, gene flow, and genetic diversity of the filial generation was studied using a random sample of 801 bulk seed from a 49-clone Pseudotsuga menziesii seed orchard. We used microsatellite DNA fingerprinting and pedigree reconstruction to assign each seed's maternal and paternal parents and directly estimated clonal reproductive success, selfing rate, and the proportion of seed sired by outside pollen sources. Unlike most family array mating system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…When the actual gametic contribution is known, then seed crops' genetic worth (represented by average breeding values weighted by parental gametic contribution) and genetic diversity (represented by effective population size) are precisely estimated (Stoehr et al 1998;Slavov et al 2005;El-Kassaby et al 2010). Gene flow within seed orchard populations is affected by three main factors; namely, 1) females' phenological asynchrony and males' fertility variation, 2) level of gene flow from external pollen sources, and 3) level of self-fertilization (Burczyk et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When the actual gametic contribution is known, then seed crops' genetic worth (represented by average breeding values weighted by parental gametic contribution) and genetic diversity (represented by effective population size) are precisely estimated (Stoehr et al 1998;Slavov et al 2005;El-Kassaby et al 2010). Gene flow within seed orchard populations is affected by three main factors; namely, 1) females' phenological asynchrony and males' fertility variation, 2) level of gene flow from external pollen sources, and 3) level of self-fertilization (Burczyk et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Given the paternal inheritance of chloroplast in conifers, cp-DNA microsatellites were also used for the same purpose (Plomion et al 2001;Stoehr et al 1998Stoehr et al , 2006. With a wider access to highly multi-allelic nuclear microsatellites, these became the markers of choice for conifers to study contamination rates in seed orchards of conifer species such Maritime pine (Pinus pinaster) (Fernandes et al 2008), Cryptomeria japonica (Moriguchi et al 2004), and Douglas Fir (Pseudotsuga menziesii) (Slavov et al 2005a); assess the outcome of SMP in Douglas Fir ; reconstruct pedigrees to correct breeding values in maritime pine (Gaspar et al 2009) and red spruce (Picea rubens) (Doerksen and Herbinger 2010;El-Kassaby et al 2010); and carry out "Breeding-without-Breeding" strategies in Douglas Fir and Larch (Larix occidentalis) (El-Kassaby et al 2011;ElKassaby and Lstiburek 2009) and Scots Pine (Pinus sylvestris) .…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted a full and partial reconstruction pedigree of lodgepole pines ( Pinus contorta ) and found that the full pedigree reconstruction was superior to the partial pedigree reconstruction, enabling the estimation of both paternal- and maternal-related fertility parameters [39]. In Douglas fir ( Pseudotsuga menziesii ), pedigree reconstruction was used to identify the maternal and paternal parents of each seed and estimate the clonal reproductive success and selfing rate and determine the proportion of seeds sired by outside pollen sources [40]. Similarly, Funda et al compared the reproductive success of three seed orchards [lodgepole pine, Douglas fir, and western larch ( Larix occidentalis )] based on pedigree reconstructions [41].…”
Section: Discussionmentioning
confidence: 99%